Paediatric urology. Issue 4 (April 2020) - Undre, Shabnam; Cherian, Abraham
Abstract: Paediatric urology is a subject that covers the urological aspects of care in children, some of which are seen also in adults, but may have specific diagnostic methods and treatments that are quite different. Additionally, it covers a range of congenital anomalies either on their own or in combination with a spectrum of disorders that need more complex management available at only specialized centres. For the purposes of a broad and basic understanding of the subject, this article will cover relevant topics and up-to-date guidelines.